A new approach for forming polymeric composite structures. (15th November 2018) - Ambrogio, G.; Conte, R.; Gagliardi, F.; De Napoli, L.; Filice, L.; Russo, P.
Abstract: The use of composite structures is increasing constantly in the last years, pushed by advantages of reduced weight and high strength. Moreover, the recent scenario points out a great attention on thermoplastic matrix composites due to their intrinsic recyclability as well for their possibility to re-use and re-manufacturing. However, the adoption of these materials can be further appreciated considering the secondary material workability as far as by demonstrating the possibility to re-manufacture the thermoplastic composite. The proposed work presents an experimental analysis carried out to investigate the downstream workability of a thermoplastic composite by one of the most versatile and flexible process. Glass fiber reinforced Polyamide 6 is the investigated material and the Single Point Incremental Forming is the implemented manufacturing approach. Since the composite matrix is characterized by a glass transition temperature higher than 50 °C, an external heating source has been necessary to perform the process in " hot" conditions. The process feasibility was fully demonstrated as well as the same was optimized in order to derive proper guidelines that can drive the process designer in the method star-up.